Characterization of biominerals in species of Canna (Cannaceae) - Barán, Enrique José (2010)
Plant biominerals are not always well characterized, although this information is important for plant physiology and can be useful for taxonomic purposes. In this work, fresh plant material of seven wild neotropical species of genus Canna, C. ascendens, C. coccinea, C. indica, C. glauca, C. plurituberosa, C. variegatifolia and C. fuchsina sp. ined., taken from different habitats, were studied to characterize the biominerals in their internal tissues. For the first time, samples from primary and secondary veins of leaves were investigated by means of infrared spectroscopy, complemented with X-ray powder diffractometry and scanning electron microscopy. The spectroscopic results, supported by X-ray powder diffractometry, suggest that the calcium oxalate is present in the form of whewellite (CaC2O4×H2O) in all the investigated samples. It is interesting to emphasize that all IR spectra obtained were strongly similar in all species studied, thus indicating an identical chemical composition in terms of the biominerals found. In this sense, the results suggest that the species of Canna show similar ability to produce biogenic silica and produce an identical type of calcium oxalate within their tissues. These results can be an additional trait to support the relationship among the families of Zingiberales.